The Effect of Short Animated Video With Captions on Students’ Vocabulary Mastery - Monica Monica; Zaitun Qamariah; Sri Normuliati (Journal on Education, 2023)
This study has examined how short animated video with captions can have effect on students' vocabulary mastery. The researcher has used quasi-experiment in this study, where there is an experimental class and a control class. The population of eighth grade students in the school studied was 271 students, while the sample taken was 60 students divided into two classes. The experimental class was treated with English language learning using short animated video with captions. Meanwhile, the control class received the treatment of learning English without the media of short animated video with captions. The results of this study showed that after the treatment there was an increase in the experimental class and the control class. However, the increase in vocabulary mastery in the experimental class obtained a higher average value than the control class. Therefore, it is found that the use of short animated video media with captions can improve students' vocabulary mastery in learning English.